Reliefs of the Phaedrus Bema in the Theatre of Dionysus in Athens: Reflections on Original Destination and Sources of Inspiration - Nalimova, Nadezhda A.; Korzun, Arina A. (Actual Problems of Theory and History of Art, 2023)
This publication deals with a wide range of issues relating to the 2nd-century relief cycle which is partly preserved in a later monument known as the Phaedrus Bema. The authors support the hypothesis that the frieze was originally a part of the stage building of the Athenian theatre and provide further arguments in favor of this statement. Four surviving slabs depict significant events from the life of Dionysus. At the same time, the frieze contains clear references to local cults, city topography, and religious festivals, thus revealing the origins of drama and Dionysiac religion in Attica. The particular emphasis on the motif of the enthroned deity in the Bema reliefs is noteworthy and should be linked to the sacred practices and cult imagery of the sanctuary of Dionysus Eleuthereus adjacent to the theatre. Apart from theological reasons, these accents may also have had political grounds in connection with the personality of Hadrian, who was titled Neos Dionysos as a patron of the Sacred Thymelic Synod. Such political, religious, and ideological messages of the Bema resonate with the sculptural setting of the Hadrianic scaenae frons, which prompts authors to consider them as parts of a single artistic unit. The connection can also be seen in the sources of inspiration. Both the reliefs and the scaena demonstrate an orientation towards a variety of iconographic and stylistic sources, monuments of different types. But in both cases, the basic idea — to represent Dionysus as the ruler of the theater receiving homage from his attendants (personified genres, Sileni-actors, and theatrical celebrities) — seems to go back to Hellenistic Dionysiaс dedications and “cult niches” with sculptural groups, such as those found on Delos and Thasos. Nevertheless, these motives were monumentalized and embedded in a new hierarchical system of images with their clear imperial overtones and reference to Hadrian’s patronage.